THE USE OF FACT QUESTION RESPONSE (FQR) STRATEGY TO IMPROVE STUDENTS’ READING ACHIEVEMENT - Dewi Sartika (Language and Education Journal, 2018)
Reading is beneficial for students to obtain new information and enlarge their knowledge. In fact, students still face some obstacles in comprehending the reading of report text. Therefore, the purpose of this study was to find out whether there was a significant difference in students’ reading achievement of report text between the students who were taught using Fact Question Response (FQR) strategy and that of those who were not. This study used quasi experimental method. The selected samples were used purposive sampling method, therefore, two classes out of seven classes. The accurate data were collected by using written test in the form of multiple choice. Based on the analyzing of independent sample t-test, the result showed that The comparison of the result of posttests between the experimental and control groups showed that the means difference of both tests was 6.08 and t-obtained (2.82) was higher than t-table (2.000) at the significant level of p<0.05. The students in the experimental group had better improvement in reading achievement because Fact Question Response (FQR) strategy guided them to survey the chapter to get general idea, to develop their way of thinking, engages the entire class to interact and share their experiences. In other words, there was a significant difference in students’ reading achievement of report text between the students